Productividad, sanidad, calidad física y perfil de los genotipos de cacao (Theobroma cacao L.) silvestres presentes en la colección de chalmers. - Sánchez Fuentes, Fabian Eduardo (2013)
The present study took place at the Pichilingue Tropical Experiment Station of INIAP, located at Kilometer 5.5 on the Quevedo–El Empalme highway in the province of Los Ríos, Ecuador. The study had as its overall objective the determination if in the High Amazon wild cacao accessions in the Chalmers collection there are outstanding genotypes in the areas of productivity, health, and flavor. Specific objectives were: 1). Understand and compare the productive and sanitary behavior of the genotypes, including the respective indices for pods and seeds. 2). Determine sensory profiles of sufficiently productive genoty peswhich allow the study of differences between profiles and taste note occurrence of any specific. Characteristics of productivity, health and sensory aspects of 73 genotypes of High Amazon cacao were evaluated using as commercial controls EET-103, IMC-67, and ICS-95 as reference for interpreting sensory variables. Measurments were taken between Dec. 2011–Dec. 2012. Variables used in the characterization and evaluation were: fresh weight (PF), number of healthy pods (MS), number of diseased pods (ME), percentage of diseased pods (%ME), number of witchesbroom (EB), number of seeds per pod (Nsem), percent cascarilla or testa (%testa), pod index (IM), and seed index (IS). Statistical analysis was basted on descriptive statistics, correlation analysis, and principal component analysis. The highest observed correlation was between healty pods (MS) and fresh weight (PF) with 0.98 significance, other correlations were negative. In the principal component analysis genotypic variability was asociated with its similarity to each one of the variables. The comparison of genoty espermitted the selection of genotypes with high productivity, which were coded as G-70, G-26, G-21, and G-5, in that order, although the distance between them was very broad. These selections were affected by moderate incidence of diseases, and the selection G-21 from having a los IS. Although genotypes with low yield, little incidence of disease, good seed indices and moderate taste profiles exist, itis difficult to find a single genotype that combines all these qualities. The database from the study of sensory variables led to selection of four genotypes with adequate sensory profiles. G-2, with a low seed index, had a combination of cacao, foral, fruity, and nut flavors; while G-70 had a moderate balance of these flavors. Genotypes G-26 and G-5 both with good productivity, had sensory profiles with elevated basic fllavors.